Optimalisasi Promosi Kesehatan Melalui Inovasi Media Visual Bagi Atlet Sepak Bola Remaja - Desty Ervira Puspaningtyas; Sri Kadaryati; Yuni Afriani; Ririn Wahyu Widayati; Siska Puspita Sari; Andika Setiawan; Cindy Nur Elityasari; Ellysha Anggreini Heryanto; Dea Puarisa Sugian Putri (MEDIA ILMU KESEHATAN, 2023)
Background: The inconsistency of performance for adolescent soccer athletes is caused by inappropriate nutrition practices. The study on U-14 to U-18 soccer athletes showed 20% of athletes lacked fluid intake and 87% of athletes had low energy and protein intake. Objective: This study aims to develop health promotion media for youth soccer athletes. Methods: This study assessed the feasibility of the developed media which consists of two stages. The first stage is the media feasibility assessment conducted by experts who focused on developing health promotion media. Results: The feasibility of sports nutrition pyramid poster, meal plate poster, and infographic is 3.2; 3.4; and 3.3. The sports nutrition pyramid poster has scores of 3 (layout); 3.5 (design); 3.2 (content). The meal plate poster has scores of 3.25 (layout); 3 (design); 3.7 (content). The infographic has scores of 3 (layout); 3 (design); 3.7 (content). There was an increase in the athlete's knowledge score from 65 to 79 (p=0.001). Conclusion: All media are feasible to be used as athletes’ health promotion media.